Improving the drum solar still performance using corrugated drum and nano-based phase change material. (25th November 2022) - Saeed, Amer A.; Alharthi, Abdulaziz M.; Aldosari, Khaled M.; Abdullah, A.S.; Essa, Fadl A.; Alqsair, Umar F.; Aljaghtham, Mutabe; Omara, Z.M.
Abstract: The problem of lack of safe drinking water is one of the problems that trouble governments all over the world. There are many methods of desalinating sea water, including solar distillers, which are used to contribute to solving this problem in places far from urbanization and not supplied with traditional energy sources and where there is an abundance of solar energy. In this work, a new design of drum solar still (DSS) was proposed to improve its productivity. The proposed design included a corrugated drum solar still (CDSS), conventional drum solar still (DSS), and conventional solar still (CSS). The DSS contained a rotating flat drum, and CDSS contained a rotating corrugated drum. These drums were operated by a DC motor connected to photovoltaic panels. In addition, the impact of using nano-painting for the CDSS and phase change material (PCM) mixed with Ag nanomaterial was tested on the CDSS performance. Besides, the effect of rotating the drum at various speeds (0.05, 0.1, 0.3, 0.5, 0.7 rpm) was tested. Additionally, environmental and economic analyses were carried out to make sure the reliability of the performance of the tested system. The experimental results showed that the yield was improved by 318 % for CDSS with corrugated drum, Ag-black paint and PCM-Ag at 0.1 rpm compared to that of CSS. In addition, the CDSS is capable to mitigate 14 tons of CO2 per year. The costs of 1 L from the CDSS and CSS were 0.039 and 0.048, respectively. Highlights: New design of corrugated drum solar still (CDSS) was tested and compared with DSS and CSS. Effect of using nano-paint and PCM-Ag nanoparticles on CDSS performance is tested. The productivity of CDSS was improved by 51 %. The productivity of CDSS with nano-paint and PCM-Ag was improved by 318 %. Amount of CO2 mitigation per year was 14 tons for the CDSS.